Hardening mechanisms in olivine single crystal deformed at 1090 °C: an electron tomography study. Issue 33 (22nd November 2017) - Mussi, Alexandre; Cordier, Patrick; Demouchy, Sylvie; Hue, Benoit
Abstract: The dislocation microstructures in a single crystal of olivine deformed experimentally in uniaxial compression at 1090 °C and under a confining pressure of 300 MPa, have been investigated by transmission electron tomography in order to better understand deformation mechanisms at the microscale relevant for lithospheric mantle deformations. Investigation by electron tomography reveals microstructures, which are more complex than previously described, composed of and dislocations commonly exhibiting 3D configurations. Numerous mechanisms such as climb, cross-slip, double cross-slip as well as interactions like junction formations and collinear annihilations are the source of this complexity. The diversity observed advocates for microscale deformation of olivine significantly less simple than classic dislocation creep reported in metals or ice close to melting temperature. Deciphering mechanism of hardening in olivine at temperatures where ionic diffusion is slow and is then expected to play very little role is crucial to better understand and thus model deformation at larger scale and at temperatures (900–1100 °C) highly relevant for the lithospheric mantle.